Onsite Non-potable Reuse for Large Buildings: Environmental and Economic Suitability as a Function of Building Characteristics and Location. (1st March 2021) - Arden, Sam; Morelli, Ben; Cashman, Sarah; Ma, Xin (Cissy); Jahne, Michael; Garland, Jay
Highlights: Rainfall and AC condensate only partially meet large building non-potable demand RWH and ACH systems require suitable climates to be competitive with MBR systems MBR systems meet all non-potable demands but more heavily rely on electricity use Benefits of thermal recovery to offset hot water heating greatly depend on grid mix WWMBR systems are generally the most cost-competitive Abstract: Onsite non-potable reuse (NPR) is a way for buildings to conserve water using onsite sources for uses like toilet flushing, laundry and irrigation. Although early case study results are promising, aspects like system suitability, cost and environmental performance remain difficult to quantify and compare across broad geographic contexts and variable system configurations. In this study, we evaluate four NPR system types – rainwater harvesting (RWH), air-conditioning condensate harvesting (ACH), and source-separated graywater and mixed wastewater membrane bioreactors (GWMBR, WWMBR) – in terms of their ability to satisfy onsite non-potable demand, their environmental impacts and their economic cost. As part of the analysis, we developed the Non-potable Environmental and Economic Water Reuse Calculator (NEWR), a publicly available U.S. EPA web application that allows users to generate planning-level estimates of system cost and environmental performance using location and basic building characteristics as inputs. By running NEWR for a range of scenarios, we find that, across the U.S., rainfall and air-conditioner condensate are only able to satisfy a fraction of the non-potable demand typical of large buildings even under favorable climate conditions. Environmental impacts of RWH and ACH systems depend on local climate and were comparable to the ones of MBR systems where annual rainfall exceeds approximately 10 in/yr or annual condensate potential exceeds approximately 3 gal/cfm. MBR systems can meet all non-potable demands but their environmental impacts depend more on the composition of the local energy grid, owing to their greater reliance on electricity inputs. Incorporation of thermal recovery to offset building hot water heating requirements amplifies the influence of the local grid mix on environmental impacts, with mixed results depending on grid composition and whether thermal recovery offsets natural gas or electricity consumption. Additional environmental benefits are realized when NPR systems are implemented in water scarce regions with diverse topography and regions relying on groundwater sources, which increases the benefits of reducing reliance on centralized drinking water services. In terms of cost, WWMBRs were found to have the lowest cost under the largest range of building characteristics and locations, achieving cost parity with local drinking water rates when those rates were more than 7 per 1000 gallons, which occurred in 19% of surveyed cities. Graphical Abstract: Image, graphical abstract